Prevalence, healthcare costs and management of non-communicable diseases in people living with human immunodeficiency virus: A scoping review - Laston Gonah; Indres Moodley; Khumbulani Hlongwana (AOSIS, 2020)
Background: Coexistence of human immunodeficiency virus (HIV) and non-communicable diseases (NCDs) is an important public health issue of increasing concern. However, the prevalence, healthcare costs and management protocols for NCDs in people living with HIV (PLHIV) remain unclear in most settings. Aim: To scope evidence on prevalence, healthcare costs and disease management protocols associated with NCDs in PLHIV from studies published before July 2019. Methods: Electronic databases were searched for published articles, and reference lists were checked for relevant studies. Key terms included were HIV/AIDS, co-morbidity or multi-morbidity, NCDs, healthcare costs, treatment protocols, diabetes mellitus, hypertension in various combinations. Results: A total of 152 records were assessed, and thereafter 25 studies were included in the final review after all the elimination. Twelve of the 25 studies mostly reported prevalence of NCDs in PLHIV, 4 reported impact of HIV-NCD co-morbidity on healthcare costs and 1 reported management protocols and capacity of antiretroviral therapy (ART) sites to manage HIV-NCD co-morbidity. Conclusions: Results showed higher prevalence rates of diabetes mellitus and hypertension in PLHIV compared with HIV-negative people. However, there was inconsistency in NCD prevalence data from studies conducted in sub-Saharan African (SSA) countries, and limited research evidence on capacity of ART sites to manage NCDs in PLHIV. Low prevalence rates of NCDs reported in SSA countries could be an indication of limited capacity to screen for NCDs because of the influence of health system and/or patient-level factors. Most studies were generally limited to cross-sectional studies, with very few interventional, longitudinal studies.